2023
DOI: 10.21037/qims-22-1420
|View full text |Cite
|
Sign up to set email alerts
|

The application of 18F-FDG PET/CT imaging for human hepatocellular carcinoma: a narrative review

Yong Yao,
A. Cahid Civelek,
Xiao-Feng Li

Abstract: Background and Objective Primary hepatocellular carcinoma (HCC) poses a significant threat to human health. The mean overall survival (OS) of HCC is approximately 15.8 months whereas the 6-month and 1-year OS rates are only 71.6% and 49.7%, respectively. 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) has been widely used for the management of several solid cancers; however, HCC frequently displays l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…However, since morphological characteristics do not incorporate the biological behavior of the tumor, PET imaging agents have been evaluated as well [60]. Generally, [ 18 F]FDG PET is not considered useful for HCC detection and it is not currently recommended for the diagnosis of HCC because of the high rate of false-negative results; conversely, [ 11 C]/[ 18 F]choline PET has demonstrated a higher detection rate and sensitivity compared to [ 18 F]FDG [61,62]. In this scenario, radiolabeled PSMA PET/CT has recently shown promising results in comparison with [ 18 F]FDG.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…However, since morphological characteristics do not incorporate the biological behavior of the tumor, PET imaging agents have been evaluated as well [60]. Generally, [ 18 F]FDG PET is not considered useful for HCC detection and it is not currently recommended for the diagnosis of HCC because of the high rate of false-negative results; conversely, [ 11 C]/[ 18 F]choline PET has demonstrated a higher detection rate and sensitivity compared to [ 18 F]FDG [61,62]. In this scenario, radiolabeled PSMA PET/CT has recently shown promising results in comparison with [ 18 F]FDG.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Surgery usually is recommended as curative therapy for early-stage HCC according to current clinical practice guidelines ( 3 , 4 ); however, about 70% of patients treated with SR and 25% of those treated with LT experience recurrence, and the 5-year overall survival (OS) rate is also unsatisfactory, at only 15–20% ( 35 ). Numerous studies have demonstrated that MVI is a strong risk factor correlated with these poor outcomes ( 1 , 5 , 9 - 12 ).…”
Section: The Clinical Importance Of MVImentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the predominant form of primary liver cancer and due to its increasing incidence and mortality, is gradually becoming a global health problem ( 1 - 3 ). In recent decades, with the advance of imaging techniques, an increasing number HCC cases are being detected at the early stage.…”
Section: Introductionmentioning
confidence: 99%